2011
DOI: 10.1007/s00330-011-2342-9
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion tensor imaging applications in multiple sclerosis patients using 3T magnetic resonance: a preliminary study

Abstract: Magnetic resonance imaging is widely performed in multiple sclerosis (MS) patients Diffusion tensor imaging (DTI) can be implemented using a 3T magnet DTI provides quantitative parameters as mean diffusivity (MD) and fractional anisotropy (FA) MD and, especially, FA can help evaluate the lesion load in MS patients and also assess variation in normal appearing white matter (NAWM) in MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 20 publications
2
9
1
Order By: Relevance
“…Concerning the spinal cord, the present study agreed with previous DTI studies of the spinal cord in MS patients reported a statistically significant FA difference between the control group and the MS patient group [3,[7][8][9][10][11]. Chen et al [7] stated that the decrease in the FA value of NAWM and the increase in MD value as compared to normal controls indicate the presence of occult damage to the NAWM.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Concerning the spinal cord, the present study agreed with previous DTI studies of the spinal cord in MS patients reported a statistically significant FA difference between the control group and the MS patient group [3,[7][8][9][10][11]. Chen et al [7] stated that the decrease in the FA value of NAWM and the increase in MD value as compared to normal controls indicate the presence of occult damage to the NAWM.…”
Section: Discussionsupporting
confidence: 90%
“…Diffusion tensor imaging (DTI) found to be more sensitive in identifying the occult tissue damage in MS patients than conventional magnetic resonance (MR) by means of accurate data about water diffusion within tissues. The DTI by its quantitative indices fractional anisotropy and mean diffusivity allows evaluation of the more widespread tissue damage occurring outside the lesions seen by conventional MRI [3].…”
Section: Introductionmentioning
confidence: 99%
“…The mean age range for MS patients in the included studies was between 27.5 and 50 years, with all studies containing cohorts of patients which were predominantly female. Four MRI metrics studied in 27 unique manuscripts had an adequate number of published studies (>4) whose raw data was presented in a manner amenable for meta-analysis: MTR (n=11) 12, 1720, 27, 28, 30, 31, 36, 39 , ADC (n=7) 23, 25, 29, 32, 33, 35, 44 , FA (n=6) 8, 13, 24, 34, 35, 40 , and MD (n=6) 8, 13, 14, 24, 34, 40 . There were 4 or less studies focused on specific quantitative MRI tissue parameters such as GRE-QSM or T1 or T2 relaxation times.…”
Section: Resultsmentioning
confidence: 99%
“…Investigations of psychiatric disorders, brain development, and epilepsy stand to benefit immensely from noninvasive delineation of connectivity. Basic and clinical neuroscience researchers have widely adopted diffusion tensor imaging (DTI) to delineate anatomic connectivity, in a broad range of settings, including brain development (Cascio et al 2007; Dubois et al 2006; Eluvathingal et al 2007; Hagmann et al 2010; Hüppi and Dubois 2006; Kasprian et al 2008), aging (Makris et al 2007; Ystad et al 2011), epilepsy (Liao et al 2011), multiple sclerosis (Testaverde et al 2012), and psychiatric and behavioral disorders (Ayling et al 2012; Sexton et al 2009; Travers et al 2012; Wang et al 2012; White et al 2008). Recognizing the importance of DTI, functional MR and other modalities in constructing connectivity models of the human brain, the NIH has initiated the Human Connectome Project, the goal of which is to “acquire and share data about the structural and functional connectivity of the human brain” (NIH 2013).…”
Section: Introductionmentioning
confidence: 99%